The Impact of Coronavirus Disease 2019 on the Disease Pattern of Oral and Maxillofacial Surgery Inpatients: A Comparative Study - Pu, Jingya Jane; McGrath, Colman Patrick; Leung, Yiu Yan; Choi, Wing Shan; Yang, Wei-fa; Li, Kar Yan; Su, Yu-xiong (Frontiers in Medicine, 2021)
Objective: Oral and maxillofacial surgery (OMFS) is a high-risk specialty involving airway and aerosol generating procedures, that is potentially of more risk in the era of Coronavirus disease 2019 (COVID-19). We aimed to identify the impact of COVID-19 on the disease pattern of OMFS inpatients and surgeries under general anesthesia in a comparative study. Materials and Methods: We reviewed the admission and operating theater records of OMFS patients from 1 Jan to 31 Aug in 2020 and 2019. Total number of cases, presenting disease patterns, proportion of essential and non-essential medical services were compared between 2020 and 2019. Results: There were 664 admissions and 356 general anesthesia surgical procedures included in this study. Compared to 2019, both admission and surgery numbers were significantly reduced in 2020 (p=0.012 and 0.007, respectively). The proportion of malignancy cases increased significantly, whereas that of cleft lip and palate and TMD decreased. There was a significant increase in the proportion of essential services compared to non-essential services in 2020 compared to 2019. Conclusion: Our results firstly reported the epidemiological data of the impact of COVID-19 on OMFS disease pattern in a comparative study. The change of disease pattern and caseload will have long-term impact on OMFS patient care, education and training during the pandemic. Our paper provides evidence for health policy makers to consider the relocation of medical resources, and optimization of medical education and services.